E.02 Streamlining hyperacute stroke management at Royal University Hospital. (17th June 2016) - Szmigielski, AJ; Whelan, R; Graham, B; Hunter, G; Peeling, L; Kelly, M
Abstract : Background: The Saskatoon stroke program participated in the ESCAPE trial looking at rapid endovascular revascularization for large vessel occlusion. Improvements were necessary to meet the timelines mandates in ESCAPE and to comply with Canadian Best Practice Guidelines.Methods: Retrospective chart review and prospective gathering of key metrics was performed using REDCap (Research Electronic Data Capture) software. Changes adapted from Canadian Best Practice Recommendations for Stroke Care, the ESCAPE protocol, and the Calgary stroke program HASTE project were implemented.Results: Changes implemented included increasing ambulance bypass window to 12 hours, FAST stroke assessment, emergency department pre-notification and registration, stroke alert protocol, team swarm of the patient, administration of tPA in the computed tomography (CT) room, and rapid access to the endovascular suite. Total number of patients between the years 2012 and 2014 was 287, and of those, 93 received tPA. Door-to-CT times decreased from 40 minutes to 21 minutes from 2012 to 2014; and Door-to-Needle (tPA) decreased from 62 minutes to 46 minutes from 2012 to 2014.Conclusions: By following Canadian best practice recommendations for stroke care, the ESCAPE protocol, and adaptation of Calgary stroke program HASTE project, our stroke program implemented changes to reduce treatment times for patients experiencing stroke in our province.